Propuesta de mejora del sistema de tratamiento de agua residual del proceso de clorinación para su reutilización en la empresa Enterna S.A. (2020)
The company Eterna S.A currently consumes a large amount of water to the different productive processes among them is the production of latex gloves, where much of the effluent is generated specifically in the chlorination phase, currently has a WTS plant where they meet all types of liquid effluents and due process is done to be able to comply with the permissible ranges of industrial dumping specified in the Resolution 0631 of 2015; however, what is sought is to decrease to a large extent the extensive consumption of drinking water in the company, that is why we are looking for a alternative for the possible reuse of the effluent generated in the phase of chlorination To solve this problem, a general description of the company was made and productive process, subsequently the water consumption was evaluated by means of a water balance to be able to perform a characterization of the different types of effluents to be treated where about seven parameters were evaluated, being these BOD5, COD, SDT, hardness, conductivity, pH, and chlorides, where studied the relevance of each of these in the process and how they affect the final product, according to this the treatment alternative was selected more suitable for treating which includes processes such as neutralization, coagulation and flocculation, filtration and ultrafiltration. After the experimental development of the processes already mentioned favorable results were obtained regarding the decrease of critical parameters selected in the effluent. Finally, we proceeded to perform the sizing of the equipment for possible implementation on an industrial scale and thus culminate with the calculation of operational and investment costs.